Expanding the biomass derived chemical space. Issue 7 (10th May 2017) - Brun, Nicolas; Hesemann, Peter; Esposito, Davide
Abstract : The derivatization and covalent modification of biomass derived platform chemicals expand the biomass derived chemical spaces allowing for the preparation of new bioactive molecules and materials. Abstract : Biorefinery aims at the conversion of biomass and renewable feedstocks into fuels and platform chemicals, in analogy to conventional oil refinery. In the past years, the scientific community has defined a number of primary building blocks that can be obtained by direct biomass decomposition. However, the large potential of this "renewable chemical space" to contribute to the generation of value added bio-active compounds and materials still remains unexplored. In general, biomass derived building blocks feature a diverse range of chemical functionalities. In order to be integrated into value-added compounds, they require additional functionalization and/or covalent modification thereby generating secondary building blocks. The latter can be thus regarded as functional components of bio-active molecules or materials and represent an expansion of the renewable chemical space. This perspective highlights the most recent developments and opportunities for the synthesis of secondary biomass derived building blocks and their application to the preparation of value added products.